2015
DOI: 10.1377/hlthaff.2014.1204
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Medicaid Churning: Extending Eligibility For Twelve Months Or To End Of Calendar Year Is Most Effective

Abstract: Medicaid churning - the constant exit and re-entry of beneficiaries as their eligibility changes - has long been a problem for both Medicaid administrators and recipients. Churning will continue under the Affordable Care Act, because despite new federal rules, Medicaid eligibility will continue to be based on current monthly income. We developed a longitudinal simulation model to evaluate four policy options for modifying or extending Medicaid eligibility to reduce churning. The simulations suggest that two op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 15 publications
0
26
0
Order By: Relevance
“…In addition, Medicaid enrollment may be short-lived, with high rates of churning in some subpopulations. 42,43 Nevertheless, Medicaid enrollment was relatively continuous in our population aged 52 to 64 years; among the 2144 patients in the parent study who were identified as eligible and were randomized to receive 1 of the 2 reminder-based programs, only 4 reported not participating because of loss of Medicaid insurance, and none of the 18 FIT-positive patients reported losing Medicaid insurance by the time of followup navigation.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, Medicaid enrollment may be short-lived, with high rates of churning in some subpopulations. 42,43 Nevertheless, Medicaid enrollment was relatively continuous in our population aged 52 to 64 years; among the 2144 patients in the parent study who were identified as eligible and were randomized to receive 1 of the 2 reminder-based programs, only 4 reported not participating because of loss of Medicaid insurance, and none of the 18 FIT-positive patients reported losing Medicaid insurance by the time of followup navigation.…”
Section: Discussionmentioning
confidence: 96%
“…Though recently reversed, the Center for Medicare and Medicaid had previously eliminated all substance use disorder claims from their available data sets, thus limiting analysis of substance‐related medical disease like ALD in persons covered by Medicare or Medicaid . Many AC patients are Medicaid‐insured due to low income and socioeconomic status, and as many as 50% of them will lose eligibility yearly due to income fluctuations, making large‐scale national analyses of this population over time challenging . Even within our well‐characterized cohort, AC prevalence may be underestimated due to failure to recognize an alcohol etiology, which has been shown to occur in other studies where mortality from ALD was underestimated by 2‐fold due to patient concealment and stigma .…”
Section: Discussionmentioning
confidence: 99%
“…More and longer gaps in insurance coverage experienced by JIY is evidence of churning, or frequent movement between publicly insured, privately insured, and uninsured status. 23 Reasons for churning include changes in insurance eligibility (eg, increased income, incarceration), acquisition of insurance from another source, or dropout of eligible recipients (eg, failing to complete required reenrollment applications). Churning for Medicaid enrollees most often reflects dropout, meaning that individuals move from public insurance rolls to uninsured status, despite continued eligibility for coverage.…”
Section: Medicaid Enrollment Continuitymentioning
confidence: 99%
“…To address access to care, several states have expanded eligibility for Medicaid or auto-enrolled eligible patients, which should reduce churning and provide greater access to affordable care. 14,23 Efforts to improve access to primary care for individuals in the justice system have targeted offenders' release from secure confinement, enrolling prisoners in Medicaid or connecting them to a primary care physician as part of standard facility discharge planning. 32,33 Given the dramatic impact of continuous Medicaid coverage on preventive care utilization among JIY ( Fig 1B), and in light of previous calls to improve Medicaid coverage for individuals involved in the justice system, 32,33 policy change to increase Medicaid enrollment for JIY remains a priority.…”
Section: Wc Visitsmentioning
confidence: 99%